Prevalence and mechanism of fluoroquinolone resistance in clinical isolates of Proteus mirabilis in Japan. Issue 3 (March 2019) - Nakano, Ryuichi; Nakano, Akiyo; Abe, Michiko; Nagano, Noriyuki; Asahara, Miwa; Furukawa, Taiji; Ono, Yasuo; Yano, Hisakazu; Okamoto, Ryoichi
Abstract: Fluoroquinolone (FQ) and cephalosporin (CEP) resistance among Enterobacteriaceae has been increasingly reported. FQ resistance occurs primarily through mutations in DNA gyrase ( gyrA and gyrB ) and topoisomerase IV ( parC and parE ). CEP resistance in Enterobacteriaceae is mainly due to the production of CTX-M type extended-spectrum β-lactamases. Although prevalence and mechanisms of FQ and CEP resistance in Enterobacteriaceae such as Escherichia coli have been well studied, little is known about Proteus mirabilis in Japan. In this study, we assessed the prevalence and mechanism of FQ resistance in Japanese clinical isolates of P. mirabilis . We collected 5845 P. mirabilis isolates from eight hospitals between 2000 and 2013. Prevalence of FQ resistance was calculated as the annual average percentage of all P. mirabilis isolates. We selected 50 isolates exhibiting susceptibility, intermediate resistance, or resistance to levofloxacin (LVX) and identified amino acid substitutions in GyrA, GyrB, ParC, and ParE. The prevalence of FQ-resistant P. mirabilis gradually increased from 2001 to 2004, reaching 16.6% in 2005, and has remained relatively high (13.3–17.5%) since then. Low-level LVX-resistant strains (MIC, 8–16 mg/L) showed significant changes in GyrB (S464Y or -I, or E466D). High-level LVX-resistant strains (MIC, 32–128 mg/L) displayed significant changes in GyrA (E87K) and ParE (D420N). The highest-level LVX-resistant strains (MIC, ≥ 256 mg/L) presented significant changes in GyrA (E87K or -G), GyrB (S464I or -F), and ParE (D420N). Our findings suggest that substitutions in GyrA (E87) and ParE (D420) have played an important role in the emergence of high-level LVX-resistant P. mirabilis isolates (MIC, ≥ 32 mg/L) in Japan.